Functional Connectomes in Time Domain from Simulated Neurotransmitter Release Based on Electrocorticograms - Zhai, You; Zhai, Jian (Frontiers in Behavioral Neuroscience, 2018)
This paper uses a newly defined functional connectome and connectome values calculated in time domain of simulated neurotransmitter release (NTR) from an electrocorticogram (ECoG) to distinguish between conditioned and unconditioned stimuli. The NTR derived from multiple channels releasing one quantum at the same time suggests that one functional connectome occurs across those channels at that time. During the first 600 ms after conditional stimulation, the connectome indexes of the 64-channel NTR trains were sorted from the 8—20 Hz band obtained from filtered rabbit ECoGs recorded from the visual cortices. In the small scale visual cortex area, this association was significantly larger than the habituation, even though the trial-to-trail variability of large scale synchrony after conditional stimulation is increased, which is also consistent with the hypothesis that attention decreases coherence of lower frequency within each cortical area. The increased conectome index suggests that the stimuli related to association are able to generate stronger substantial responses in the small scale visual cortex than habituation. That is, besides of the background cortical states as well as attention-related decreases in synchrony of lower frequency, the increased part of neurotransmitters released simultaneously from the pre-synaptic terminals of small scale visual cortex for association is larger than habituation.